Prosociality in Cyberspace: Developing Emotion and Behavioral Regulation to Decrease Aggressive Communication - Veiga Simão, Ana (2021)
Different forms of verbal aggression are often present in cyberbullying, which may impair executive function skills that enable the regulation of emotions and behavior. Emotion and behavioral regulation has been associated with better social adjustment and more positive interactions between peers. This study aimed to understand if fostering emotion and behavioral regulation strategies could decrease aggressive communication. A quasi-experimental longitudinal design, based on a Twitter client mobile application, with pre-posttest measures was used. For the application, we explored different machine learning approaches, including computational intelligence methods. Multilevel linear modeling and frequency analyses were performed. A convenience sample of 218 adolescents (M age=14.67, SD=0.84, 53% female) participated in the study. Results suggest that a Twitter client mobile application intervention based on emotion and behavioral regulation strategies may help decrease adolescents’ aggressive communication. Moreover, female and male participants who used the digital application tended to present distinct trajectories over time with regard to searching for information concerning prosocial behavior. These findings suggest that digital tools resorting to emotion and behavioral regulation strategies may be effective in reducing an aggressive communication style amongst adolescents, and consequently, promote resource seeking to engage in prosociality. These results can be significant for the design of intervention programs against cyberbullying.